Influence of Venus topography on the zonal wind and UV albedo at cloud top level: The role of stationary gravity waves. Issue 6 (30th June 2016) - Bertaux, Jean‐Loup; Khatuntsev, I. V.; Hauchecorne, A.; Markiewicz, W. J.; Marcq, E.; Lebonnois, S.; Patsaeva, M.; Turin, A.; Fedorova, A.
Abstract: Based on the analysis of UV images (at 365 nm) of Venus cloud top (altitude 67 ± 2 km) collected with Venus Monitoring Camera on board Venus Express (VEX), it is found that the zonal wind speed south of the equator (from 5°S to 15°S) shows a conspicuous variation (from −101 to −83 m/s) with geographic longitude of Venus, correlated with the underlying relief of Aphrodite Terra. We interpret this pattern as the result of stationary gravity waves produced at ground level by the uplift of air when the horizontal wind encounters a mountain slope. These waves can propagate up to the cloud top level, break there, and transfer their momentum to the zonal flow. Such upward propagation of gravity waves and influence on the wind speed vertical profile was shown to play an important role in the middle atmosphere of the Earth by Lindzen (1981) but is not reproduced in the current GCM of Venus atmosphere from LMD. (Laboratoire de Météorologie Dynamique) In the equatorial regions, the UV albedo at 365 nm varies also with longitude. We argue that this variation may be simply explained by the divergence of the horizontal wind field. In the longitude region (from 60° to −10°) where the horizontal wind speed is increasing in magnitude (stretch), it triggers air upwelling which brings the UV absorber at cloud top level and decreases the albedo and vice versa when the wind is decreasing in magnitude (compression). This picture is fully consistent with the classical view of Venus meridional circulation, with upwelling at equator revealed by horizontal air motions away from equator: the longitude effect is only an additional but important modulation of this effect. This interpretation is comforted by a recent map of cloud top H2 O, showing that near the equator the lower UV albedo longitude region is correlated with increased H2 O. We argue that H2 O enhancement is the sign of upwelling, suggesting that the UV absorber is also brought to cloud top by upwelling. Key Points: At equator the Venus zonal wind at cloud top level is discovered to vary with geographic longitude Stationary gravity waves generated by winds on orography at ground may decelerate the winds higher The UV albedo geographic map is anticorrelated to H2 O map suggesting upwelling of UV absorber